2000
DOI: 10.1128/jvi.74.6.2840-2846.2000
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Colocalizes to Mitochondria with a Human Voltage-Dependent Anion Channel, HVDAC3, and Alters Its Transmembrane Potential

Abstract: Understanding the mechanism(s) of action of the hepatitis B virus (HBV)-encoded protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
251
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(286 citation statements)
references
References 38 publications
17
251
1
3
Order By: Relevance
“…In addition to this accepted marker of mitochondrial stress, maintenance of the mitochondrial membrane potential (MMP) is also utilized as a marker of mitochondrial function [17,18,24,38]. We have shown that these two events correlate with increased mitochondrial fission and mitophagy, contributing to cell death in an infection dependent manner [24].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this accepted marker of mitochondrial stress, maintenance of the mitochondrial membrane potential (MMP) is also utilized as a marker of mitochondrial function [17,18,24,38]. We have shown that these two events correlate with increased mitochondrial fission and mitophagy, contributing to cell death in an infection dependent manner [24].…”
Section: Resultsmentioning
confidence: 99%
“…HBx exerts powerful effects on mitochondria either directly owing to their channel-forming activity or indirectly through interactions with endogenous channels (Takada et al, 1999;Henkler et al, 2001;Lee et al, 2004). HBx reportedly interacts with at least two mitochondrial proteins, namely heat-shock protein 60 and 70 (Tanaka et al, 2004;Zhang et al, 2005b) and the VDAC isoform VDAC3 (Rahmani et al, 2000;Kim, 2005).…”
Section: Hbxmentioning
confidence: 99%
“…HBx acts as a transcriptional co-activator in the nucleus and stimulates various signal transduction pathways in the cytoplasm. In addition, HBx is often found localized at the mitochondria [6][7][8]. HBx targeting to mitochondria causes a loss of mitochondrial membrane potential that has been linked to cell death [9] and oxidative liver injury [10].…”
Section: Introductionmentioning
confidence: 99%